Salivary detection of H1N1 virus: a clinical feasibility investigation - Bilder, L; Machtei, E E; Shenhar, Y; Kra-Oz, Z; Basis, F (Journal of dental research, 2011)
The fast and efficient transportation among continents will continue to play a role in the spread of airborne pandemics. The objective of this study was to detect H1N1 virus in the saliva of individuals who visited the emergency department and were diagnosed as having H1N1 influenza. Nasopharyngeal swabs and saliva samples from those who presented to the emergency department with flu-like symptoms were sent to the laboratory. RNA was extracted from both samples. Real-time RT-PCR tests were performed, and the saliva and nasopharyngeal swab tests were compared. Samples were drawn from 26 individuals. A positive nasopharyngeal swab test and salivary test was found in 14 persons, and negative tests were found in 12 persons. Saliva sampling for H1N1 has excellent predictive value, is highly accurate and reliable, and is more convenient than the nasopharyngeal swab. Clinical trial with the Helsinki Committee at Rambam Health Care Campus, registration number 036309-RMB.